2020
DOI: 10.1007/s11926-020-00913-8
|View full text |Cite
|
Sign up to set email alerts
|

Spondyloarthritis on the Move: Biomechanical Benefits or Harm

Abstract: Purpose of review Physical activity is beneficial in several diseases including spondyloarthritis despite mechanical stress being suggested as a trigger of disease onset or activity. Moreover, there is no clear answer as to where physiological loading of the joints ends and pathological overloading begins.The aim of this review is to provide an overview of what is known about exercise and biomechanical loading in spondyloarthritis.Recent findings Recent studies focused on the impact of mechanical loading in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Compared to AS, axPsA patients can be asymptomatic, have asymmetrical sacroiliitis, present worse degree of peripheral arthritis, and may present with or without sacroiliitis. However, compared to axPsA, AS patients are more likely to be male, younger, and have more limitation of spinal mobility and back pain 6 …”
Section: Axial Spondyloarthritis Axial Psoriatic Arthritis Similaritiesmentioning
confidence: 99%
“…Compared to AS, axPsA patients can be asymptomatic, have asymmetrical sacroiliitis, present worse degree of peripheral arthritis, and may present with or without sacroiliitis. However, compared to axPsA, AS patients are more likely to be male, younger, and have more limitation of spinal mobility and back pain 6 …”
Section: Axial Spondyloarthritis Axial Psoriatic Arthritis Similaritiesmentioning
confidence: 99%
“…Several other studies showed that axSpA patients working in physically demanding occupations had more loss of function and radiological damage than patients with more sedentary jobs 21 and that greater mechanical stress was associated with more severe lumbar myofascial stiffness in axSpA patients 22 23 . Microtrauma is therefore hypothesized to have a significant impact on entheses, triggering inflammation and osteoproliferation 24 . Furthermore, the relationship between post-inflammatory changes, like fat metaplasia as a precursor, and an increased risk of new bone formation in the spine 25 and SIJs 26 has also been investigated.…”
Section: Pathogenesis Of Axspamentioning
confidence: 99%
“…Not surprisingly, mechanical stress has also been linked to inflammatory rheumatic diseases such as RA, PsA, and AS (136). Here, physical trauma has been associated with disease initiation and structural progression (137,138).…”
Section: Mechanical Forces Might Drive Entheseal and Articular Inflammationmentioning
confidence: 99%